2002
DOI: 10.1590/s0101-20612002000100005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da vida-de-prateleira de bebidas lácteas preparadas com "fat replacers" (Litesse e Dairy-lo)

Abstract: RESUMOFace ao aumento de peso e ao aparecimento de doenças cardiovasculares na população mundial devido ao consumo de alimentos altamente calóricos, o desenvolvimento de alimentos com baixo ou reduzido teor de gordura torna-se essencial. Estudou-se o efeito da adição de "fat replacers" (Litesse e Dairy-lo) na vida-de-prateleira de bebidas lácteas. No presente trabalho as variáveis independentes Litesse (X 1 ) e Dairy-lo (X 2 ) foram empregadas nas concentrações 0,50,1,50, 2,50% em peso, com 7 combinações calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
2
2
0
9
Order By: Relevance
“…As seen in Figure 3, the majority of the panelists assigned scores between 6 and 9 (6 = like slightly, 9 = extremely like) for dairy beverages. Similar values were observed by Sivieri and Oliveira (2002) in their sensory evaluation of dairy beverages containing fat substitutes. In this study, the addition of inulin did not influence the sensory acceptance of the beverage because no significant differences were observed between formulations PI and C. Similarly, Isik et al (2011) observed that the addition of inulin did not affect the sensory acceptance of frozen yogurt.…”
Section: Sensory Analysissupporting
confidence: 85%
“…As seen in Figure 3, the majority of the panelists assigned scores between 6 and 9 (6 = like slightly, 9 = extremely like) for dairy beverages. Similar values were observed by Sivieri and Oliveira (2002) in their sensory evaluation of dairy beverages containing fat substitutes. In this study, the addition of inulin did not influence the sensory acceptance of the beverage because no significant differences were observed between formulations PI and C. Similarly, Isik et al (2011) observed that the addition of inulin did not affect the sensory acceptance of frozen yogurt.…”
Section: Sensory Analysissupporting
confidence: 85%
“…The analysis of data allowed observing that during the storage period of milk drinks, pH showed a considerable reduction, since the initial pH ranged from 4.13 (Treatment 1) to 4.09 (Treatment 4), reaching 3.91 (Treatment 1) and 4.00 (Treatment 4) on day 29 of storage. Similar pH results were reported by Sivieri and Oliveira (2002), who analyzed milk drinks prepared with "fatreplacers" during 28 days of storage. The pH values at baseline ranged from 4.0 to 4.6, and after 28 days of storage, it ranged from 3.9 and 4.5.…”
Section: Parameterssupporting
confidence: 86%
“…pH decreased noticeably (0.14 to 0.32 pH units) during the first week of storage ( Figure 2). Ellis (1996) found similar results for yogurts, and Sivieri and Oliveira (2002) for lactic beverages prepared with fat substitutes. Thereafter, pH slightly decreased (less than 0.12 pH units) and could be considered stable.…”
Section: Stabilitymentioning
confidence: 79%